Hypothesis and Theory: Evaluating the Co-Evolution of the Melanocortin-2 Receptor and the Accessory Protein MRAP1 - Dores, Robert M.; Chapa, Emilia (Frontiers in Endocrinology, 2021)
The melanocortin receptors (MCRs) and the MRAP accessory proteins belong to distinct gene families that are unique to the chordates. During the radiation of the chordates, the melancortin-2 receptor paralog (MC2R) and the MRAP1 paralog (melanocortin-2 receptor accessory protein 1) have co-evolved to form a heterodimer interaction that can influence the ligand selectivity and trafficking properties of MC2R. This apparently spontaneous interaction may have begun with the ancestral gnathostomes and has persisted in both the cartilaginous fishes and the bony vertebrates. The ramifications of this interaction had profound effects on the hypothalamus/anterior pituitary/adrenal-interrenal axis of bony vertebrates resulting in MC2R orthologs that are exclusively selective for the anterior pituitary hormone, ACTH, and that are dependent on MRAP1 for trafficking to the plasma membrane. The functional motifs within the MRAP1 sequence and their potential contact sites with MC2R are discussed. The ramifications of the MC2R/MRAP1 interaction for cartilaginous fishes are also discussed, but currently the effects of this interaction on the hypothalamus/pituitary/interrenal axis is less clear. The cartilaginous fish MC2R orthologs have apparently retained the ability to be activated by either ACTH or MSH-sized ligands, and the effect of MRAP1 on trafficking varies by species. In this regard, the possible origin of the dichotomy between cartilaginous fish and bony vertebrate MC2R orthologs with respect to ligand selectivity and trafficking properties is discussed in light of the evolution of functional amino acid motifs within MRAP1.